Issues around conducting prehospital research on out-of-hospital cardiac arrest: lessons from the TOPCAT study. Issue 8 (29th May 2010) - Lyon, Richard M; Egan, Gerry; Gowens, Paul; Andrews, Peter; Clegg, Gareth
Abstract : Outcome from OHCA is primarily determined by prehospital events and meaningful clinical OHCA research must include data recorded in this setting. There is little evidence on which to base the practice of prehospital resuscitation and research in this area presents huge challenges but is required if survival from OHCA is to improve. This short report aims to provide a practical guide to performing prehospital research on OHCA, based on lessons learned from the Temperature Post Cardiac Arrest (TOPCAT) research; an observational study into OHCA.